The Effect of Entrepreneurial Marketing Perceptions on MSMEs Business Performance During Covid-19 Pandemic in Bogor City - Rinda Tri Wijayanti; Mukhamad Najib; Mimin Aminah (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
This study aims to analyze the factors that affect the business performance of Micro, Small and Medium Enterprises (MSMEs) during the COVID-19 pandemic in Bogor City. The research was carried out during January-February 2021 on 150 MSME respondents with the criteria of a food processing business, a minimum business age of 2 years or have opened a business before the pandemic period. The data processing method employed in the form of quantitative descriptive analysis, cross-tabulation and using the SEM-PLS. The results showed that the characteristics of the business doers described by gender, age, educational background, reasons for pursuing a business, initial work before starting a business, the beginning of running a business, length of business which reflected by age and education level had a correlation with production techniques on internal environmental factors. External environmental factors have a significant positive effect on entrepreneurial marketing and performance which are explained by government policy aspect, socio-cultural and economic aspect, role of related institutions aspect and aspect of competitors, from these indicator variables, socio-cultural and economic aspects most reflect the external environment from the business doers. Internal environmental factors have a positive and significant effect on entrepreneurial marketing, but on the contrary, the higher the internal environmental factors, the lower the business performance. Entrepreneurial marketing shows a significant and positive influence on the business performance of MSMEs in Bogor City with a proactive indicator that can reflect entrepreneurial marketing, while business performance is reflected by the customer growth indicator. Keywords: business performance, business environment, COVID-19 pandemic, entrepreneurial marketing, MSMEs